Effects of Artificial Intelligence in Capitalist Societies; Use of Social Networks: Artificial Intelligence, Social Networks and Relationship with Stakeholders - Paredes Serrano, Cristina; Gismera Tierno, Eduardo; Zapatero González, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The use of social networks has been the subject of study in recent years without conceptual, legal or ethical consensus. We published in Comred years ago the preamble that now presents its latest advances. It was said that companies influence the behaviors of their employees on social networks, but the evolution of social changes in our system and the emergence of Artificial Intelligence accelerate the need for a regulatory framework in this regard. These changes outdated the legislation on the right to privacy and self-image. The qualitative analysis forms the guide that suggests legislating against violated rights.